Electromagnetic-Thermal Modeling of Nonlinear Magnetic Materials - Li, Hongliang; Krein, Philip T; Jin, Jian-Ming (IEEE journal on multiscale and multiphysics computational techniques, 2023)
A nonlinear electromagnetic (EM)-thermal coupled solver is developed for modeling ferromagnetic materials widely used in electric motors. To accurately predict machine performance, the time-domain finite element method is employed to solve this multiphysics problem. By adopting the nonlinear B-H models to account for hysteresis effects, magnetic core losses are computed as the major sources of power dissipation for magnetic materials. The resulting temperature change is then obtained and its effect on the magnetic properties is subsequently evaluated. Due to different time scales of EM field variations and heat transfer processes, different time step sizes are adopted to enhance the simulation speed. During thermal time marching, the EM solver is invoked adaptively based on material property changes, and EM losses are calculated and updated through extrapolation, resulting in an efficient EM-thermal coupling scheme. Numerical examples are presented to validate the accuracy and capabilities of the proposed EM-thermal co-simulation framework.